AVALIAÇÃO DA QUALIDADE DE VIDA RELACIONADA A SAÚDE DE MULHERES PORTADORAS DE CÂNCER DE MAMA. - SILVA, Igor Marcelo Castro e (2018)
Introduction: Breast cancer is one of the most feared diseases among women, having a significant social impact, especially, as to what the diagnosis and treatment entail in the quality of life of these patients. Goal: to evaluate quality of life related to the health of women with breast cancer undergoing chemotherapy at a unit of reference in cancer in the municipality of São Luís, capital of the State of Maranhão. Methodology: Descriptive, cross-sectional research. Case series: It was evaluated 57 women with breast cancer under chemotherapy treatment. It was collected clinical data and performed the interview at the time of infusion. The interview comprised of the application of the quality of life instruments, European Organization for Research and Treatment of Breast Cancer-Specific Quality of Life Questionnaire (EORTC QLQ C30 and BR-23). The data were statistically analyzed by the software Statistica 7.0, applying the ANOVA one-way test, Shapiro-Wilk test and Levene's test, with a significance level of 0.05. Results: the average age of the women is 52.54 (± 10,371), married, from the capital, housewives, white, own their houses, have been to high sedentary, have undergone radical surgical intervention, us sec haonothl,r caactyhcolilnice, associated to cyclophosphamide. Physical function and cognitive function detained the higher scores in the EORTC QLQ C30. Sexual function and satisfaction had the greatest scores in the EORTC QLQ C23. The overall Quality of Life (QOL) was considered to be reasonable satisfactory. We observed a statistically significant relationship between the averages of QOL and staging. The values of QOL increase proportionally to the emotional and social functions scores. On the other hand, QOL data are inversely proportional to the values of constipation, loss of appetite, nausea and vomiting, and pain. It was evidenced that the lower QOL values and future prospects, the greater the values of breastrelated symptoms, arm-related symptoms, and side effects. Conclusion: The quality of life as an indicator of health provides the health care professional the awareness of the real situation of the patient, who can then manage the physical and social readaptation of the woman with breast cancer.